The production of scientific knowledge about teaching self-efficacy: review study in the physical education field - Kuhn, Filipy (2019)
Objective: The objective of this study was to conduct a survey and analysis of the production of theses, dissertations and empirical articles published in the last 10 years, related to the Physical Education area, on the subject of teacher self-efficacy (TSE). Systematic review procedures were adopted to carry out this research. Methods: The research was divided into two stages, namely: a survey of theses and dissertations was carried out, in the journal of Coordination for the Improvement of Higher Education Personnel, to select postgraduate programs. Next, a search was made for the selection of empirical articles in the electronic databases: Academic Search Premier; Cinahl; Google Scholar; Medline; Scielo; Science Direct; Scopus; and Web of Science. Results: In relation to the results obtained in the analysis of the theses and dissertations produced, it was verified that of the 33 universities investigated, only three contained research related to the AED topic. About the results of the articles, only six were selected. Conclusion: Based on the reading of theses, dissertations and articles, it can be seen that university students have high AED, especially when placed in a supervised internship.